Adverse event reporting and patient safety: the role of a just culture - Kumah, Augustine (Frontiers in Health Services, 2025)
Reporting adverse events is essential for ensuring patient safety and fostering a culture of continuous improvement in healthcare. Adverse events, defined as unintended injuries or complications arising from healthcare management, offer crucial insights into systemic weaknesses that, if addressed, can prevent future harm. However, underreporting such events remains a significant challenge, often driven by fear of punitive actions, reputational damage or legal repercussions. To address these concerns and promote a robust reporting culture, healthcare organisations must adopt a just culture by implementing standardised frameworks for evaluating errors and establishing robust reporting systems. A culture that emphasises accountability and learning over punitive measures. Leadership commitment, psychological safety, and fair accountability are foundational to fostering a just culture in healthcare. While each theme presents specific requirements and challenges, their integration is essential for building a resilient and learning-oriented healthcare system.